STUDY OF FECAL GLUCOCORTICOID METABOLITE IN BEARS: A REVIEW - Zoumin, Elden; Siti Sarayati Hj. Abdul Mawah,; Lo Chor Wai (Dr.),; Farnidah Jasnie, (Malaysian Journal of Science, 2023)
Fecal glucocorticoid metabolite (FGM) analysis is a non-invasive method to monitor animals' welfare in captivity and wild environments. Glucocorticoid also known as cortisol is a hormone that indicates the level of stress in animals and humans. This paper reviews the use of FGM analysis on bears and the methodologies used to study this hormone in every species of bear. The review method used was descriptive review. The bears that were included in this review are the brown bear (Ursus arctos), Polar bear (Ursus maritimus), Asiatic black bear (Ursus thibetanus), American black bear (Ursus americanus), Malayan sun bear (Helarctos malayanus), sloth bear (Melursus ursinus), Andean spectacled bear (Tremactos ornatus), and giant panda (Ailuropodia melanoleuca). Studies of FGM on polar bears showed that zoo-to-zoo transportation could cause an increase in FGM level during transportation and FGM is not suitable to be used to differentiate between pseudo-pregnancy and true pregnancy. In Malayan sun bear, FGM level is high in female bears that show agonistic behavior and is associated with low progesterone levels. In addition, studies on Malayan sun bear show that not only FGM can be analyzed from fecal samples, but also the reproductive hormones of estrogen and progesterone. In Asiatic black bears, FGM is higher in bears that live in a bile farm than forage outside the forest reserve. High parasite load in giant pandas is associated with a high level of FGM since parasite infection is considered a stressor that can elicit a stress response. Also both male and female panda have high FGM during the breeding season to increase metabolism to generate energy required for reproductive activities. The Alopecia syndrome in Andean spectacled bear has no significant relation to FGM level. Brown bears with several types of food in their diet have lower FGM than those with only one type of food. There is no specific study of FGM that focused on sloth bear and American black bear, but there were several studies on glucocorticoid in black bears that are not extracted from fecal samples. FGM can be analyzed using both enzyme-immunoassay (EIA) and radioimmunoassay (RIA) but, EIA is preferable due to safety reasons.